Exploring the role of digital servitization for sustainability: A framework for environmental and social impact - Elena Beducci; Federica Acerbi; Anna De Carolis; Marco Taisch (Cleaner Environmental Systems)
In the manufacturing context, servitization emerges as a relevant path to improve sustainability. Notably, it can be applied to reconfigure industries' business models into circular ones, through multiple sustainable and circular strategies. Digital servitization, particularly, can enhance companies' sustainability along the products’ lifecycle, optimizing design and operations through collected data and supporting decision-making for end-of-life activities.Digitalization, servitization, and sustainability present promising synergies, nonetheless this topic requires more research. It is possible to observe a lack of understanding of the intersection of servitization, digitalization, and sustainability, and how they can be applied in the manufacturing context.This paper aims to investigate the connection between digital technologies, services, and sustainable strategies. The objective is to identify and characterize the linkages between digital technologies, services, and environmental and social sustainable strategies in the context of servitization. Through the implementation of a systematic literature review, the paper proposes an analysis of the state-of-the-art, identifying main trends and investigating specific relevant digital technologies, services, and sustainable impacts. The authors then propose a framework which clarifies how services, enabled by specific digital technologies, can be leveraged in the context of manufacturing product service systems to implement social and environmental sustainability strategies. Finally, the paper highlights opportunities for future research based on existing identified gaps.